Use of the ilizarov method of distraction osteogenesis for the treatment of radial hemimelia in a dog - Rahal, Sheila C.; Volpi, Reinaldo S.; Ciani, Renata B.; Vulcano, Luiz C. (American Veterinary Medical Association (AVMA), 2005)
Radial hemimelia (congenital absence of the radius) is uncommon in dogs. Correction of radial hemimelia by use of surgical procedures incorporating the Ilizarov method of distraction osteogenesis is an alternative to amputation of the limb.